Advanced methods for geological interpretation of depositional environments and lithofacies: insights into hydrocarbon potential in the northern Norwegian North Sea - Al Janabi, Ali; Knapp, Camelia C.; Albesher, Ziyad (Frontiers in Earth Science, 2025)
Exploration in the northern Norwegian North Sea is limited by complex Paleogene stratigraphy and underexplored stratigraphic traps in the Sele and Lista formations due to ambiguous well logs and scarce core data. This study addresses the critical scientific challenge of accurately characterizing these formations to assess their hydrocarbon potential. To resolve this problem, the study integrates gamma-ray log motifs, high-resolution core imagery, and lithofacies analysis from thirty-nine wells across quadrants 31, 32, 35, 36, and 6204. Eleven stratigraphic cross-sections were constructed in both dip and strike directions to analyze vertical stacking patterns, depositional environments, and key stratigraphic surfaces such as sequence boundary and maximum flooding surface. Thirteen distinct lithofacies were identified and grouped into four depositional types: low-energy mudstones, turbidites, sandy debris flows, and muddy debris flows. These facies were further assessed for reservoir quality attributes, including porosity, permeability, and net-to-gross ratio. The findings reveal that the Lista Formation contains laterally extensive, sand-rich turbidites and debris flows with significant reservoir potential, while the Sele Formation is predominantly mud-rich, serving as a regional seal. A key contribution of this study is the development of a 3D structural depth model that enhances the spatial understanding of lithofacies distribution and reservoir connectivity. The integrated methodology presented here improves geological interpretation and supports exploration in deep-water environments. As stratigraphic traps become increasingly critical exploration targets, especially in mature basins, this integrated approach supports reservoir characterization on a global scale. This study enhances the geoscientific understanding of post-rift basin evolution and stratigraphy in the Norwegian North Sea and provides a methodological framework that can be applied to similar deep-marine offshore systems around the world.